Mepacrine Flow Cytometry Assay for the Diagnosis of Platelet δ-granule Defects: Literature Review on Methods—Towards a Shared Detailed Protocol - Khourssaji, Mehdi; Bareille, Marion; Alberio, Lorenzo; Borgel, Delphine; Fouassier, Marc; Béné, Marie-Christine; Lecompte, Thomas; Mullier, François (Thrombosis and Haemostasis, 2024)
Accurate assessment of platelet secretion is essential for the diagnosis of inherited or acquired platelet function disorders and more specifically in identifying δ-storage pool disease. Mepacrine, a fluorescent dye, specifically accumulates in platelet δ-granules. The mepacrine flow cytometry (mepacrine FCM) assay has been used for more than half a century in the clinical laboratory as a diagnostic tool for platelet δ-granule disorders. The assay requires a small volume of blood, can be performed in thrombocytopenic patients, provides rapid assessment of δ-granule content and secretion, and, thus, enables differentiation between storage and release defects. There is however a broad heterogeneity in methods, reagents, and equipment used. Lack of standardization and limited data on analytical and clinical performances have led the 2022 ISTH SSC (International Society on Thrombosis and Haemostasis Scientific and Standardization Committee) Subcommittee on Platelet Physiology expert consensus to rate this assay as simple but of uncertain value. Yet, the data used by experts to formulate the recommendations were not discussed and even not mentioned. Guidance for laboratory studies of platelet secretion assay would be very helpful for clinical laboratories and health authorities especially considering the implications of the new In Vitro Diagnostic Regulation in Europe. The purpose of the present work was to review the reported methodologies for the mepacrine FCM assay and to offer an example of detailed protocol. This would help standardization and pave the way for more rigorous comparative studies.
Keywords: mepacrine; flow cytometry; storage pool disease; platelet; inherited or acquired diseases; delta granule